2003
DOI: 10.1590/s1516-89132003000300020
|View full text |Cite
|
Sign up to set email alerts
|

A modified method for the turbidimetric assay of nisin

Abstract: Nisin is an antibacterial peptide produced by Lactococcus lactis subsp. lactis that shows a broad spectrum of inhibitory activity against gram-positive microorganism including bacterial spores. Methods for nisin activity estimation in solution is redefined. In this work a new turbidimetric assay method has been described making possible to assay nisin satisfactorily in total incubation period of approximately six hours.
Nisina é um peptídeo antibacteriano produzido por Lactococcus lactis subsp lactis que ap…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The supernatant was carried on corn starch at 1:9 W/W and then dried at 40°C for 24 h; therefore, each 1 g of BLS contained 100 mg bacteriocin and 900 mg corn starch as a carrier. The bioassay of the produced BLS was conducted as described by Flôres et al (2003). Briefly, one tube of Lactococcus lactis subsp.…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant was carried on corn starch at 1:9 W/W and then dried at 40°C for 24 h; therefore, each 1 g of BLS contained 100 mg bacteriocin and 900 mg corn starch as a carrier. The bioassay of the produced BLS was conducted as described by Flôres et al (2003). Briefly, one tube of Lactococcus lactis subsp.…”
Section: Methodsmentioning
confidence: 99%
“…Further attempts are made to develop a quantitative method using automated turbidometry to assess the antimicrobial efficacy of bacteriocin-like inhibitors produced by pseudomonas aeruginosa, pediococus dammosus and pediococcus pentosaccus and the growth of the test strain namely pseudomonas aeruginosa was kinetically monitored and various growth curve parameters were used as quantitative indicators of inhibition 14 . Flores 15 , et al reported a modified turbidimetric assay method for nisin in total incubation period of approximately 6 h. using Lactococcus lactis subsp. cremoris as test microorganism.…”
Section: Introductionmentioning
confidence: 99%